Gamma Radiation influence on Growth, Biochemical and Yield Characters of Cajanus cajan (L.) Millsp. - N. Seetharaman, M. Ariraman, D. Dhanavel,; R. Ramkumar, S. Murugan, (Journal of Plant Stress Physiology)
The present investigation deals with the effect of gamma radiation on growth, Biochemical and yield traits of Pigeon pea. The seeds of Pigeon pea Var.CO-7 were treated with different doses of gamma rays like 15, 20 and 25KR. The treated seeds were sown in field along with control to raise M1 generation and the radiation effects was noted from seed germination percentage, seedling survival (%), seedling height on 30th days, Days to first flower, plant height, (at maturity), number of branches, number of leaves, number of cluster, pollen viability (%), number of pods, seed yield, hundred seed weight (g), fresh and dry weight (g), Seed viability (%) and seed protein content (%). The results indicates that the growth, biochemical and yield parameters were gradually decreased when compare to control and the highest reduction was noted at higher doses of gamma radiation treatments. The pollen and seed viability (%) analysis were also reveled that gradually reduction in lower to higher doses of gamma rays treatments.